ID170 Cost-utility of Pilates versus home-based exercises in individuals with chronic non-specific low back pain: economic evaluation alongside a randomised controlled trial - Carregaro, Rodrigo Luiz; Tottoli, Caroline Ribeiro; Ben, Ângela Jornada; Silva, Everton Nunes da; Bosmans, Judith E.; Tulder, Maurits van (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2024)
Introduction Chronic non-specific low back pain (CNLBP) is a major cause of disability resulting in high healthcare and lost productivity costs worldwide. Exercise therapy is the most prescribed treatment for CNLBP worldwide. Despite the benefits of exercise therapy, systematic reviews have highlighted the need for further high-quality evidence regarding their (cost-)effectiveness related to alternative treatments such as Pilates. Therefore, the aim was to investigate the cost-effectiveness of Pilates compared with home-based exercises for CNLBP.